Pengembangan Aplikasi Raiz-Texture (Raiz-Telolet Excretory Adventure) untuk Meningkatkan Hasil Belajar Pada Materi Sistem Ekskresi - Budiarto, Rais (SCAD Independent, 2024)
This study aims to examine the effectiveness of the RAIZ-TEXTURE (Raiz-Telolet Excretory Adventure) application in improving student learning outcomes on the excretory system material, as well as to describe the development process carried out using the ADDIE Research and Development model. Specifically, the study investigates students’ initial learning outcomes before using the application (pretest), the steps involved in designing and developing RAIZ-TEXTURE, the learning outcomes after its implementation (posttest), and the overall effectiveness of the media in supporting student achievement. This research was conducted using an R&D approach with five stages—Analysis, Design, Development, Implementation, and Evaluation—over a period of five months from May to September 2017. The subjects consisted of 39 students of class XI MIA 1 MAN Tenggarong, preceded by a small-group trial involving five students to evaluate the initial feasibility of the application. The pretest results showed that none of the students reached the Minimum Completion Criteria (KKM), indicating a low initial understanding of the excretory system. Through the ADDIE process, the RAIZ-TEXTURE application was successfully developed as an interactive learning medium that supports visual, conceptual, and exploratory learning. After implementation, the posttest results demonstrated a significant improvement, with 94.87% of students achieving classical completeness above the KKM. The effectiveness analysis produced a high effectiveness score of 0.7384 (73.84%), showing that the RAIZ-TEXTURE application substantially enhances student learning outcomes on the excretory system material. Thus, this application serves as an effective and engaging digital learning tool for biology instruction.